Culture of impact in agricultural research organisations: What for and how? - Ferré, Marie; Blundo Canto, Genowefa; Rodrigues, Geraldo Stachetti; Ramírez Gomez, María Margarita; Vedovoto, Graciela Luzia; Agudelo Chocontá, Beatriz Elena; Marques, Daniela Vieira; Valladao Flores, Roberto Manolio; Rodríguez Borray, Gonzalo Alfredo; de Souza, Mirian Oliveira; Goulet, Frédéric; Vásquez Urriago, Angela Rocío; et al. (Elsevier B.V., 2025)
Research organisations experience increasing demands to analyse on the multidimensional societal impacts of their activities. This leads to more reflections about the integration of organisational strategies devoted to research evaluation and impact monitoring, in order to answer societal and funder’s demands, improve research practices, and make research and innovations more transformative to society. Establishing a “culture of impact” within an organisation is driven by multiple factors and translates into a variety of changes at different organisational levels. We aim to understand what motivates agricultural research organisations to develop a culture of impact, and the consequences of this culture on research, management, and collaboration practices. For this, we analyse organisational trajectories of three research organisations: the French Agricultural Research Centre for International Development (Cirad), the Brazilian Agricultural Research Corporation (Embrapa), and the Colombian Agricultural Research Corporation (AGROSAVIA). Through a cross-analysis of these cases along the reasons to integrate impact evaluation in strategic agendas, the materialisation of a culture of impact in practice, and what it entails in terms of cognitive and practical changes within their respective staff and management structures, we highlight drivers and patterns of development of a culture of impact, and circumstances that seem to either favour or hinder its emergence. This study is unique for examining various types of changes that a culture of impact can generate among individuals, in particular. It offers valuable material to enable reinterrogate and orient a research organisation’s culture of impact’s path in accordance with organisational values, priorities, and opportunities.